Do pinch points and barriers affect functional connectivity for butterflies and grasshoppers across networks of conservation corridors? - Davids, Liaam (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhDConsEcol)--Stellenbosch University, 2025.